2006
DOI: 10.1016/j.jaci.2005.12.1348
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin in inner-city homes: Associations with wheeze and eczema in early childhood

Abstract: Background-An inverse association between domestic exposure to endotoxin and atopy in childhood has been observed. The relevance of this aspect of the "hygiene hypothesis" to U.S. innercity communities that have disproportionately high asthma prevalence has not been determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
118
5
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 143 publications
(135 citation statements)
references
References 38 publications
9
118
5
2
Order By: Relevance
“…In a cohort of 1,884 German newborns, a two-fold increased risk of wheezing during the first 6 months of life was found in children exposed to high endotoxin concentrations (OR 2.37, 95% CI 1.40-4.03) [78]. Such associations have been confirmed in other longitudinal studies [79,80,84], as well as in case-control or crosssectional studies [81][82][83]. Moreover, exposure to endotoxins has been linked to asthma severity and morbidity [86,87].…”
Section: Endotoxinssupporting
confidence: 59%
See 2 more Smart Citations
“…In a cohort of 1,884 German newborns, a two-fold increased risk of wheezing during the first 6 months of life was found in children exposed to high endotoxin concentrations (OR 2.37, 95% CI 1.40-4.03) [78]. Such associations have been confirmed in other longitudinal studies [79,80,84], as well as in case-control or crosssectional studies [81][82][83]. Moreover, exposure to endotoxins has been linked to asthma severity and morbidity [86,87].…”
Section: Endotoxinssupporting
confidence: 59%
“…Findings from epidemiological studies are less consistent [74]. Whereas some reports suggest a protective effect of endotoxins on the development of allergies [57,[75][76][77], others found that the exposure to endotoxins constitutes a risk factor for respiratory symptoms [78][79][80][81][82][83][84], which might depend on the amount of exposure [85].…”
Section: Endotoxinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although endotoxin exposure might be related to rural exposure to pets and other farm animals, Litonjua et al 14 found that in Boston the effects of pet and endotoxin exposure were separate and contrary. Similarly, although endotoxin levels in this NYC cohort were related to wheeze and rhinitis, 21 they neither were related to pet ownership nor affected the associations between pet ownership and wheeze/rhinitis in logistic regression.…”
Section: Discussionmentioning
confidence: 60%
“…[18][19][20][21] Exclusion criteria included a diagnosis of diabetes or HIV infection, reported illicit drug use, and residency in NYC for less than 1 year before pregnancy. Between the years 1998 and 2006, 2844 mothers were screened during pregnancy, and 725 were fully enrolled, which was defined as participation in prenatal assessments and cord blood collection at birth.…”
Section: Study Cohortmentioning
confidence: 99%